Enablers and constraints of creation and sharing of knowledge assets: a case of NGO policy advocacy - Salazar García, LM (2005)
This dissertation aims to develop and validate a conceptual framework about the enablers and constraints for the creation and sharing of knowledge assets. Knowledge assets are understood as a subset of dispositions to act that is embedded in individuals, groups or artefacts and that allows us to economise the consumption of resources for a given amount of effort (Boisot 1998). The creation of knowledge assets within organisations is seen as a knower-dependent, social and non-linear process of learning that builds on information. Enablers and constraints can be found at any part of this learning process and differ from one information environment to another. The theoretical framework integrates Boisot's Social Learning Cycle (SLC) with an Information Ecology model in order to identify the potential enablers and constraints within specific information environments. The empirical setting chosen for this research is a group of leading international nongovernmental organisations (INGOs) and their domestic NGO partners, pursuing a policy advocacy strategy in the context of a high-level international donors conference. Policy advocacy refers to a set of activities directed towards influencing decision makers in a way that contributes to benefiting disadvantaged populations. Advocate INGOs and their domestic NGO partners (advocacy communities) gain influence by becoming alternate sources of information to decision makers (Keck and Sikkink 1998); their ability to create and share knowledge assets is then critical. The research is based on an in-depth case study and qualitative analysis techniques (Eisenhardt 1989; Yin 1989; Marshall and Rossman 1995), focusing on two levels: Intra-organisational and inter-organisational. The collection of data covers a one-year period (February 2003 to February 2004). The focus on a complex information environment, represented here by transnational advocacy communities, proves valuable in expanding existing theory about the dynamics of the creation and sharing of knowledge assets in and between organisations. The data collected suggests that most constraints are of internal nature and are centred on the value exploiting stage of the SLC. Constraints associated with organisations' cultures, individuals' information processing preferences, and politics are prominent.